The art of storytelling in Old Javanese prose as illustrated by the story of Ekalawya - van der Molen, Willem (Wacana, Journal of the Humanities of Indonesia, 2016)
Scholarly attention for Old Javanese literature so far has mainly focused on poetry. The apparently simple nature of narrative prose texts, while making them excellent sources for linguistic and lexicographic research, at the same time denies them any literary value. In this article an impression is given of the art of storytelling in one Old Javanese prose story, taken from the Adiparwa of around A.D. 1000. Quite unexpectedly, a sophisticated tradition unfolds in which a rich variety of devices enables the storyteller to create a meaningful world of words.